The role of the Pangandaran Regency DPRD in Forming Regional Regulations that are Responsive to Community Needs - Galih Ridwan Syaori; Fika Febriani; Dhea Diva Rahayu; Arie Budiawan (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
The Regional People's Representative Council (DPRD) of Pangandaran Regency plays a pivotal role in formulating Regional Regulations (Perda) through its legislative function, collaborating with the local government (executive). The Perda formation process involves systematic stages: (1) legislative program drafting based on legal needs analysis and regional development plans (RPJMD); (2) academic manuscript review covering philosophical, juridical, and sociological aspects; (3) in-depth discussion by a Special Committee (Pansus); and (4) enactment through plenary meetings and official gazetting. Implementation of Perda, such as the Tourism Village Regulation (No. 4/2022), demonstrates success despite persistent challenges. Currently, the target of establishing four Perda/year is underway, emphasizing public participation and legal harmonization. Policy reviews highlight sustainable tourism, local economic empowerment, and climate adaptation, with ongoing evaluations to ensure regulatory effectiveness.